Telestration with augmented reality for visual presentation of intraoperative target structures in minimally invasive surgery: a randomized controlled study - Wild, Caroline Johanna; Lang, Franziska; Gerhäuser, Annabelle Sofia; Schmidt, Mona Wanda; Kowalewski, Karl-Friedrich; Petersen, J.; Kenngott, Hannes Götz; Müller, Beat P.; Nickel, Felix (Surgical endoscopy and other interventional techniques, 2022)
In minimally invasive surgery (MIS), intraoperative guidance has been limited to verbal communication without direct visual guidance. Communication issues and mistaken instructions in training procedures can hinder correct identification of anatomical structures on the MIS screen. The iSurgeon system was developed to provide visual guidance in the operating room by telestration with augmented reality (AR).
Gesehen am 11.09.2023